Friedrich Rathgen and his impact on Slovenian Conservation in the beginning of the twentieth century - Nataša Nemeček (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Friedrich Rathgen can be directly linked to the Slovene provinces or, more exactly, to the Duchess of Mecklenburg. In 1906, Rathgen visited her at Castle Bogenšperk, and received some prehistoric finds for conservation. Other highly interesting links to the history of conservation and restoration of archaeological objects are the 1913 excavations in Stična, where the duchess excavated the famous Stična armour. Once more, the finds were sent to Berlin for restoration.